Щодо організації викладання правових дисциплін в медичних та фармацевтичних навчальних закладах III-IV рівнів акредитації - Туманський, Валерій Олексійович; Алексєєв, Олександр Германович; Tumanskiy, V. A.; Alekseev, A .G. (Запорізький державний медичний університет, 2008)
We have realized the theoretical ground on the law practical subjects. It is suitable for Ukrainian demands (like country with the Law Code), National Law teaching programme which are based on the Balonsky prosses. We have carried out the complex teaching programme "Law Code of professional activity of doctor and pharmaceutics regulation" at the medical (pharmaceutical) university Law causes.
The organization of Law teaching practical subjects at the medical and pharmaceutical department ill-IV levels of accreditation
Keywords: законодавство з охорони здоров'я; правова навчальна дисципліна; правове регулювання професійної діяльності лікаря та провізора; aw Code of Health Care; Law Code lake the Studying discipline; Law Code of professional activity of doctor and pharmaceutics regulation